An extension of the TALDICE ice core age scale reaching back to MIS 10.1. (15th August 2021) - Crotti, Ilaria; Landais, Amaelle; Stenni, Barbara; Bazin, Lucie; Parrenin, Frédéric; Frezzotti, Massimo; Ritterbusch, Florian; Lu, Zheng-Tian; Jiang, Wei; Yang, Guo-Min; Fourré, Elise; Orsi, Anais; et al.
Abstract: TALDICE (TALos Dome Ice CorE) is a 1620 m deep ice core drilled at Talos Dome, an ice dome located at the edge of the East Antarctic Plateau in the Ross Sea Sector. The Antarctic Ice Core Common Chronology (AICC2012) extended the age scale of the core until ∼150 ka (1438 m depth) (Bazin et al., 2013), while no age scale was available below 1438 m depth. In this work we present the new TALDICE-deep1 chronology using the new measurements of δ 18 Oatm, δD and 81 Kr as well as the inverse model IceChrono1. The TALDICE-deep1 chronology stops at 1548 m, as the portion below this depth is probably affected by mixing processes. The new age scale extends the climate record for the Ross Sea Sector of the East Antarctic Ice Sheet back to MIS 10.1–343 ka (1548 m depth) and identifies both MIS 7 and 9 warm stages, which show specificities in the δD signal. However, it is not possible to recover the isotopic record beyond stage 10.1 as the signal shows a quasi-flat shape. Thereby, the new chronology TADICE-deep1 doubles the extension of the previous age scale as it covers the three past glacial/interglacial cycles. Highlights: Multi-approach and multi-proxy data set provided a new age scale for the deep portion of the TALDICE ice core. Two additional glacial-interglacial cycles identified in the extremely thinned deep part of the TALDICE ice core. First application of the krypton dating technique to define an ice core age scale. Anomalous water stable isotope signals during past warm periods from an East Antarctic peripheral ice core.